Penerapan Mediasi Pada Penyelesaian Perselisihan Hubungan Industrial - Agnes Widiana Putri; Hermanto Silalahi; Diah Imaningrum S (Comprehensive Law Journal, 2023)
Industrial Relations Disputes occur between parties due to differences in opinions or ways of viewing matters that occur in the company. Settlement of industrial relations disputes, namely rights disputes, layoff disputes, interest disputes, disputes between SP/SB. Efforts are made by choosing to use mediation, conciliation or arbitration. The problem that arises is how to implement mediation in resolving industrial relations disputes at the Malang Regency Labor Relations Department and the supporting and inhibiting factors in the level of success in resolving industrial relations disputes at the Malang Regency Labor Relations Service. This research uses qualitative research methods using a Sociological Juridical approach. Efforts that must be made by the parties to resolve their disputes must first be through bipartite negotiations, and registered with the Department. If the parties do not choose, then the parties will use mediation to resolve the dispute. However, for parties who do not agree in mediation, the mediator will make written recommendations to the parties within 10 (ten) working days and must be given an answer to the recommendation. If they refuse, the parties will proceed to court, but if they accept, then a PB will be made and registered. to PHI. Obstacles during the mediation process as an effort to resolve industrial relations disputes occur among the parties, but can also occur with the mediator and the Malang district labor office, such as the parties not understanding labor laws, good faith in attending the mediator's summons, a strong sense of wanting to win for themselves. owned by the parties. For the mediator himself, he lacks experience in hearings and the human resources needed are very lacking. For the Malang district labor department itself, there is a lack of facilities and infrastructure for holding meetings. Obstacles during the mediation process as an effort to resolve industrial relations disputes occur among the parties, but can also occur with the mediator and the Malang district labor office, such as the parties not understanding labor laws, good faith in attending the mediator's summons, a strong sense of wanting to win for themselves. owned by the parties. For the mediator himself, he lacks experience in hearings and the human resources needed are very lacking. For the Malang district labor department itself, there is a lack of facilities and infrastructure for holding meetings.